A fully automatic AI system for tooth and alveolar bone segmentation from cone-beam CT images - Zhiming Cui; Yu Fang; Lanzhuju Mei; Bojun Zhang; Bo Yu; Jiameng Liu; Caiwen Jiang; Yuhang Sun; Lei Ma; Jiawei Huang; Yang Liu; Yue Zhao; et al. (Nature Communications, 2022)
Accurate delineation of individual teeth and alveolar bones from dental cone-beam CT images is an essential step in digital dentistry for precision dental healthcare. Here, the authors present a deep learning system for efficient, precise, and fully automatic segmentation of real-patient CBCT images presenting highly variable appearances.